2018
DOI: 10.1534/genetics.117.300606
|View full text |Cite
|
Sign up to set email alerts
|

A Failsafe for Sensing Chromatid Tension in Mitosis with the Histone H3 Tail inSaccharomyces cerevisiae

Abstract: Mitotic fidelity is ensured by achieving biorientation on all paired chromosomes. The key signal for proper chromosome alignment is the tension between sister chromatids created by opposing poleward force from the spindles. In the budding yeast, the tension-sensing function requires that the Shugoshin protein, Shugoshin 1, be recruited to the centromeres and the neighboring pericentric regions. Concerted actions integrating proteins at centromeres and pericentromeres create highly specific Shugoshin 1 domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…Although not reliant on G34 or K36 residues of H3, SGO1 binds a ‘tension-sensing motif’ at residues 42–45 on H3, which is necessary for Sgo1 recruitment to centromeres and for efficient chromosome segregation during mitosis ( Deng and Kuo, 2018 ; Luo et al, 2016 ). Intriguingly in this system, the histone acetyltransferase Gcn5 is important for ensuring efficient chromosome segregation when the tension sensing motif is damaged ( Buehl et al, 2018 ; Luo et al, 2016 ). It is not clear whether Shugoshin proteins in higher organisms show a similar dependence on N-terminal regions of H3 for their localization and whether H3.3-G34R mutation influences their localization.…”
Section: Discussionmentioning
confidence: 99%
“…Although not reliant on G34 or K36 residues of H3, SGO1 binds a ‘tension-sensing motif’ at residues 42–45 on H3, which is necessary for Sgo1 recruitment to centromeres and for efficient chromosome segregation during mitosis ( Deng and Kuo, 2018 ; Luo et al, 2016 ). Intriguingly in this system, the histone acetyltransferase Gcn5 is important for ensuring efficient chromosome segregation when the tension sensing motif is damaged ( Buehl et al, 2018 ; Luo et al, 2016 ). It is not clear whether Shugoshin proteins in higher organisms show a similar dependence on N-terminal regions of H3 for their localization and whether H3.3-G34R mutation influences their localization.…”
Section: Discussionmentioning
confidence: 99%
“…Although not reliant on G34 or K36 residues of H3, SGO1 binds a "tension sensing motif" at residues 42-45 on H3, which is necessary for Sgo1 recruitment to centromeres and for efficient chromosome segregation during mitosis Luo, Deng, Buehl, Xu, & Kuo, 2016). Intriguingly in this system, the histone acetyltransferase Gcn5 is important for ensuring efficient chromosome segregation when the tension sensing motif is damaged (Buehl et al, 2018;Luo et al, 2016). It is not clear whether Shugoshin proteins in higher organisms show a similar dependence on N-terminal regions of H3 for their localization and whether H3.3-G34R mutation influences their localization.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent findings that Gcn5p acts as a negative regulator for tension sensing motif and Sgo1p functional interaction (L uo et al 2016; B uehl et al 2018) alludes to an intriguing possibility that Gcn5p, acetylated H3, or a downstream effector may prevent Sgo1p from binding to the chromosome arms. ChIP-seq data show a lack of correlation between Gcn5p and these Sgo1p-free valleys in mitosis (Figure 3), arguing against a direct, physical role of Gcn5p.…”
Section: Discussionmentioning
confidence: 99%
“…The budding yeast Shugoshin, Sgo1p , was first identified as a protector of meiotic cohesin against precocious cleavage ( K itajima et al 2004 ), and later found to be also crucial for cells to activate the SAC in coping with tensionless conditions in mitosis ( I ndjeian et al 2005 ). Expressed in S and M phases of the cell cycle ( I ndjeian et al 2005 ; E shleman and M organ 2014 ), Sgo1p is localized to centromeres and pericentromere ( K iburz et al 2005 ; F ernius and H ardwick 2007 ; K iburz et al 2008 ) without stashing a significant extrachromosomal pool ( B uehl et al 2018 ). Shugoshin is recruited to centromeres by binding to histone H2A phosphorylated by the Bub1 kinase ( K awashima et al 2010 ; L iu et al 2013a ).…”
mentioning
confidence: 99%
See 1 more Smart Citation